Studi tentang kegiatan pengembangan koleksi terbitan berkala pada Dinas Perpustakaan dan Kearsipan Daerah Provinsi Jawa Barat - Sri Parti Nurani; Yunus Winoto (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2019)
ENGLISH This study aims to determine the periodical collection collection activities. The location of this study was conducted at the Regional Library and Archives Service Office of West Java Province. The method used in this study is a qualitative research method with the technique of collecting data through interviews, observation and documentation studies. Based on the results of the study, it is known that the activities of developing periodical collections in the Library and Archives Office of West Java Province